Reflection of Bratislava retail network in selected aspects of consumer behaviour - Kita, Pavol; Grossmanová, Marta (Business: Theory and Practice, 2014)
The paper analyses the evolution of the retail network of the capital city of Slovakia Bratislava affecting buying behavior and lifestyle of its consumers. From the marketing point of view, it characterizes the current retail network in Bratislava and presents the main trends in the development of retail stores in Bratislava. It shows, on the one hand, how the importance of consumer behaviour rise in the decline economic prosperity during last years, while on the other hand, how the concentration in retail declines the chances for success of small independant food retail stores during last recent years. The authors used methodes, e. g. multidimentional scaling, GIS, for testing assesses the significance of these changes on the sample involving 11.389 repondents interviewed. The paper presents the results of research project VEGA No. 1/0039/11 Geographical Information System as a Source of Strategic Innovation of Enterprise from the Point of View of Strengthening its Competitiveness.